Greater glucose uptake heterogeneity in knee muscles of old compared to young men during isometric contractions detected by [18F]-FDG PET/CT - Rudroff, Thorsten; Kindred, John H.; Benson, John-Michael; Tracy, Brian L.; Kalliokoski, Kari K. (Frontiers in Physiology, 2014)
We used positron emission tomography/computed tomography (PET/CT) and [18F]-FDG to test the hypothesis that glucose uptake (GU) heterogeneity in skeletal muscles as a measure of heterogeneity in muscle activity is greater in old than young men when they perform isometric contractions. Six young (26 ± 6 yrs) and six old (77 ± 6 yrs) men performed two types of submaximal isometric contractions that required either force or position control. [18F]-FDG was injected during the task and PET/CT scans were performed immediately after the task. Within-muscle heterogeneity of knee muscles was determined by calculating the coefficient of variation (CV) of GU in PET image voxels within the muscles of interest. The average GU heterogeneity (mean ± SD) for knee extensors and flexors was greater for the old (35.3 ± 3.3 %) than the young (28.6 ± 2.4 %) (P = 0.006). Muscle volume of the knee extensors were greater for the young compared to the old men (1016 ± 163 vs. 598 ± 70 cm3, P= 0.004). In a multiple regression model, knee extensor muscle volume was a predictor (partial r = - 0.87; P = 0.001) of GU heterogeneity for old men (R2 = 0.78; P < 0.001), and MVC force predicted GU heterogeneity for young men (partial r = - 0.95, P < 0.001). The findings demonstrate that glucose uptake is more spatially variable for old than young men and especially so for old men who exhibit greater muscle atrophy.